Arctic strategy of the United States: Development, challenges and prospects - Filijović Marko; Kilibarda Zoran (Војно дело, 2016)
The Arctic region has been attracting increasing attention of world political and academic community. The credit for that goes, first of all, to identified hydrocarbon and other resources, which, due to thawing of ice caused by climate change, finally became available. Striving to “get a fair share” in the situation of constant growth in demand for energy, the majority of states bordering the coast of the Arctic Ocean decided to regulate the matter of the division of this not yet fully lotted-up world region under the United Nations Convention on the Law of the Sea (UNCLOS). The exception are the United States, which have not yet ratified the document, although they clearly show an intention to exploit the Arctic resources. The paper analyzes the development of the US political, military and economic engagement in the Arctic region. The focus of the analysis is to examine the current challenges faced by Washington in this area, with addressing special attention to the suggestions of scientific and political communities for the possible ways of their timely overcoming.